Iatrogenic complications after laparoscopic cholecystectomy and prevention of their complications - Usmoov Xusniddin Qutbidinovich (Genius Journals, 2022)
In the current article, the causes of iatrogenic injuries were studied in 1890 laparoscopically performed cholecystectomy operations and in 84 patients after it. By dividing them into three groups according to time, complications were eliminated in selected operative methods. It was stated that the post-operative periods of these patients were analyzed and the stenotic complications were identified and eliminated by modern methods
Keywords: Cholecystectomy; iatrogenic complications; external liver tumors